Identifying Circular RNAs in HepG2 Expressing Genotype IV Swine Hepatitis E Virus ORF3 Via Whole Genome Sequencing. (26th October 2021) - Jiao, Hanwei; Zhao, Yu; Zhou, Zhixiong; Li, Wenjie; Li, Bowen; Gu, Guojing; Luo, Yichen; Shuai, Xuehong; Fan, Cailiang; Wu, Li; Chen, Jixuan; Huang, Qingzhou; et al.
Swine hepatitis E (SHE) is a new type of zoonotic infectious disease caused by swine hepatitis E virus (SHEV). Open reading frame 3 (ORF3) is a key regulatory and virulent protein of SHEV. Circular RNAs (circRNAs) are a special kind of non-coding RNA molecule, which has a closed ring structure. In this study, to identify the circRNA profile in host cells affected by SHEV ORF3, adenovirus ADV4-ORF3 mediated the overexpression of ORF3 in HepG2 cells, whole genome sequencing was used to investigate the differentially expressed circRNAs, GO and KEGG were performed to enrichment analyze of differentially expressed circRNA-hosting gene, and Targetscan and miRanda softwares were used to analyze the interaction between circRNA and miRNA. The results showed adenovirus successfully mediated the overexpression of ORF3 in HepG2 cells, 1, 105 up-regulation circRNAs and 1, 556 down-regulation circRNAs were identified in ADV4-ORF3 infection group compared with the control. GO function enrichment analysis of differentially expressed circRNAs-hosting genes classified three main categories (cellular component, biological process and molecular function). KEGG pathway enrichment analysis scatter plot showed the pathway term of top20. The circRNAs with top10 number of BS sites for qRT-PCR validation were selected to confirmed, the results indicated that the up-regulated hsa_circ_0001423 and hsa_circ_0006404, and down-regulated of hsa_circ_0004833 and hsa_circ_0007444 were consistent with the sequencing data. Our findings first preliminarily found that ORF3 protein may affect triglyceride activation (GO:0006642) and riboflavin metabolism (ko00740) in HepG2 cells, which provides a scientific basis for further elucidating the effect of ORF3 on host lipid metabolism and the mechanism of SHEV infection.